Theoretical study about L-arginine complexes formation with thiotriazolin - L. I. Kucherenko; O. V. Hromyleva; I. A. Mazur; S. V. Shishkina (Zaporožskij Medicinskij Žurnal)
Brain vascular diseases are one of the leading causes of morbidity, mortality and disability of population in the industrialized countries of the world. An important element of this problem’s solution is the creation of new highly effective and safe drugs, which would lead to mortality reduction, to increase in life expectancy and quality of life. Therefore it is interesting to create a new combined drug based on L-arginine and thiotriazolin.